Studies on the Metabolic Error in Refsum's Disease - Steinberg, Daniel (1967)
Studies utilizing mevalonic acid-2-(14)C and D(2)O as precursors failed to provide evidence for an appreciable rate of endogenous biosynthesis of phytanic acid in a patient with Refsum's disease. Orally administered tracer doses of phytol-U-(14)C were well absorbed both by seven normal control subjects (61 to 94%) and by two patients with Refsum's disease (74 and 80%). The fraction of the absorbed dose converted to (14)CO(2) in 12 hours was 3.5 and 5.8% in Refsum's disease patients and averaged 20.9% in seven control subjects. Labeled phytanic acid was demonstrated in the plasma of both control subjects and patients given phytol-U-(14)C, establishing phytol in the diet as a potential precursor of phytanic acid. This labeled phytanic acid had disappeared almost completely from the plasma of the seven control subjects by 24 to 48 hours, whereas it persisted at high concentrations in the plasma of the two patients for many days. We conclude that the phytanic acid accumulating in Refsum's disease is primarily of exogenous origin and that patients with Refsum's disease have a relative block in the degradation of phytanic acid and possibly other similar branched-chain compounds. This may relate to a deficiency in mechanisms for release of phytanic acid from stored ester forms or, more probably, to reactions essential to oxidative degradation of the carbon skeleton.